1975
DOI: 10.1161/01.res.37.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Transmural gradients in ventricular tissue metabolites produced by stopping coronary blood flow in the dog.

Abstract: To determine whether transmural metabolite gradients develop in the contracting, ischemic left ventricle due to factors other than a nonuniform distribution of myocardial blood flow, right and left coronary artery inflow was completely stopped with vessel occluders in open-chest dogs for 15 or 30 seconds before a transmural myocardial tissue sample was obtained for regional analysis of creatine phosphate, adenosine triphosphate (ATP), and lactate. Heart rate was controlled, and the decline in left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(31 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…The variations that occur in the myocardium in metabolic rate (Griggs et al 1972, Dunn andGriggs 1975), oxygenation (Gamble et al 1974;Schubert et al 1978;Weiss and Sinha 1978), and myocardial fiber shortening (LeWinter et al 1975) have become generally recognized. Similarly, the spatial heterogeneity of regional myocardial blood flow has been clearly demonstrated with indicator dilution methods (Bassingthwaighte et al 1972;Rose and Goresky 1976;Roselli and Harris 1979) and with the microsphere technique (Yipintsoi et al 1973;Falsetti et al 1975;Marcus et al 1977;Sestier et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The variations that occur in the myocardium in metabolic rate (Griggs et al 1972, Dunn andGriggs 1975), oxygenation (Gamble et al 1974;Schubert et al 1978;Weiss and Sinha 1978), and myocardial fiber shortening (LeWinter et al 1975) have become generally recognized. Similarly, the spatial heterogeneity of regional myocardial blood flow has been clearly demonstrated with indicator dilution methods (Bassingthwaighte et al 1972;Rose and Goresky 1976;Roselli and Harris 1979) and with the microsphere technique (Yipintsoi et al 1973;Falsetti et al 1975;Marcus et al 1977;Sestier et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Following coronary artery occlusion, myocardial lactate becomes elevated within 15 seconds, and creatine phosphate is decreased by this time; ATP begins to fall within 30 seconds (Dunn and Griggs, 1975). A rise in extracellular potassium has been reported to occur within 30 seconds (Hill and Gettes, 1977), and the earliest pH decrease was found at 15 seconds (Benzing et al, 1971/72).…”
Section: Discussionmentioning
confidence: 99%
“…Under these anaerobic circumstances, h-oxidation, citric acid cycle and electron transport chain cannot take place (Fig 4). Several studies have shown that during ischemia differences exist in metabolism between the subepicardium and subendocardium, resulting in a more rapid depletion of energy stores in the subendocardium compared to the subepicardium, in analogue to the perfusion differences found with microspheres [20][21][22]. These differences in metabolism can be explained by several reasons.…”
Section: Myocardial Metabolism During Ischemiamentioning
confidence: 99%